2021
DOI: 10.2196/32544
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Telehealth Interventions for Women With Postpartum Depression: Systematic Review and Meta-analysis

Abstract: Background Postpartum depression (PPD) is a prevalent mental health problem with serious adverse consequences for affected women and their infants. Clinical trials have found that telehealth interventions for women with PPD result in increased accessibility and improved treatment effectiveness. However, no comprehensive synthesis of evidence from clinical trials by systematic review has been conducted. Objective The aim of this study is to evaluate the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 47 publications
0
28
1
Order By: Relevance
“…To date there have been only a few eHealth-related meta-analyses, including four looking at online or technology-assisted parenting programs (Florean et al, 2020 ; Harris et al, 2020 ; Spencer et al, 2020 ; Thongseiratch et al, 2020 ) and one of telehealth family therapy programs (McLean et al, 2021 ), all with parent mental health as secondary outcomes. Some recent meta-analyses have also examined eHealth interventions for postpartum mental health (Feng et al, 2021 ; Zhao et al, 2021 ; Zhou et al, 2020 ), which represents a distinct period with unique challenges and care provisions where treatment needs and content would differ from that after infancy. However, there have been no systematic reviews or meta-analyses of the literature that identifies the effectiveness of a broader range of eHealth programs on mental health among parents of young children, specifically.…”
Section: Introductionmentioning
confidence: 99%
“…To date there have been only a few eHealth-related meta-analyses, including four looking at online or technology-assisted parenting programs (Florean et al, 2020 ; Harris et al, 2020 ; Spencer et al, 2020 ; Thongseiratch et al, 2020 ) and one of telehealth family therapy programs (McLean et al, 2021 ), all with parent mental health as secondary outcomes. Some recent meta-analyses have also examined eHealth interventions for postpartum mental health (Feng et al, 2021 ; Zhao et al, 2021 ; Zhou et al, 2020 ), which represents a distinct period with unique challenges and care provisions where treatment needs and content would differ from that after infancy. However, there have been no systematic reviews or meta-analyses of the literature that identifies the effectiveness of a broader range of eHealth programs on mental health among parents of young children, specifically.…”
Section: Introductionmentioning
confidence: 99%
“…Two articles [ 51 , 57 ] reported that electronic intervention was ineffective in relieving anxiety, and another [ 59 ] showed mixed views. Electronic intervention was reported to be ineffective for depression in 2 studies [ 51 , 60 ], whereas 3 articles [ 54 , 55 , 59 ] provided mixed conclusions. There were mixed results regarding the effect of pain relief, with some studies [ 50 , 51 ] indicating no effect on pain relief, and others [ 55 , 61 ] reporting the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of quality of life, 3 studies [49][50][51] reported that electronic interventions were ineffective, but 7 [52][53][54][55][56][57][58] reported improvement in quality of life. Two articles [51,57] reported that electronic intervention was ineffective in relieving anxiety, and another [59] showed mixed views. Electronic intervention was reported to be ineffective for depression in 2 studies [51,60], whereas 3 articles [54,55,59] provided mixed conclusions.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…38 In addition to the limited inclusion of studies among child/adolescent populations, there were few studies conducted in populations with psychotic disorders that were included in the meta-analyses. All reviews limited their searches to publications in English, apart from Zhao et al, 41 which also included Chinese language publications. Table 1 shows additional characteristics of the included meta-analytic reviews.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%